Perspectives of people with diabetes on AI-integrated wearable devices: perceived benefits, barriers, and opportunities for self-management - Alzghaibi, Haitham (Frontiers in Medicine, 2025)
AbstractWearable devices that incorporate artificial intelligence (AI) have become effective instruments for managing diabetes through real-time monitoring, improved adherence, and increased person with diabetes engagement. Person with diabetes perceptions, adoption barriers, and preferences critically impact the effectiveness and widespread utilisation of these technologies.AimThe aim of study was to investigate the perceptions of people with diabetes regarding wearable devices, emphasising their perceived advantages, challenges, and potential role in facilitating diabetes self-management.MethodsA cross-sectional study involving 418 people with diabetes was conducted, with participants recruited via online platforms and people with diabetes groups. Data were gathered through a structured questionnaire that included Likert-scale items, multiple-choice questions, and open-ended responses. Descriptive statistics were employed to analyse quantitative data, whereas qualitative responses underwent thematic analysis to discern key trends.ResultsParticipants demonstrated significant awareness of the primary functions of wearable devices, with 83.9% acknowledging their utility in monitoring glucose levels and physical activity. The primary advantages comprised increased adherence to medication regimens (81.9%) and heightened confidence in diabetes management (82.1%). Significant barriers were identified, including data privacy concerns (79.7%), cost issues (77.0%), and usability challenges (75.1%). Thematic analysis of open-ended responses indicated a demand for features including actionable feedback, integration with healthcare providers, and enhanced usability. Despite these challenges, 81.9% of participants indicated a willingness to adopt AI-integrated wearable devices if recommended by healthcare providers.ConclusionThe findings indicate that people with diabetes regard wearable devices as effective instruments for managing their condition, especially in terms of real-time monitoring and adherence support. Concerns regarding privacy, cost, and device usability must be addressed to enhance adoption rates. These insights can inform the development of patient-centered wearable devices and guide healthcare strategies for the effective integration of these technologies into diabetes care.